2021
DOI: 10.1038/s41419-021-04473-2
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor I-C disrupts cellular homeostasis between autophagy and apoptosis via miR-200b-Ambra1 in neural tube defects

Abstract: Impaired autophagy and excessive apoptosis disrupt cellular homeostasis and contribute to neural tube defects (NTDs), which are a group of fatal and disabling birth defects caused by the failure of neural tube closure during early embryonic development. However, the regulatory mechanisms underlying NTDs and outcomes remain elusive. Here, we report the role of the transcription factor nuclear factor I-C (NFIC) in maintaining cellular homeostasis in NTDs. We demonstrated that abnormally elevated levels of NFIC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The prevalence of NTDs is estimated to be 18.6 per 10,000 live births ( Finnell et al, 2021 ). Babies with NTDs are more likely to be stillborn, die shortly after birth, or develop different degrees of disability ( Huang et al, 2021 ). The etiology of NTDs is complex and is associated with interactions between genetic factors and diverse environmental factors ( Avagliano et al, 2019 ; Kakebeen and Niswander, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NTDs is estimated to be 18.6 per 10,000 live births ( Finnell et al, 2021 ). Babies with NTDs are more likely to be stillborn, die shortly after birth, or develop different degrees of disability ( Huang et al, 2021 ). The etiology of NTDs is complex and is associated with interactions between genetic factors and diverse environmental factors ( Avagliano et al, 2019 ; Kakebeen and Niswander, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…15 of them present a transcriptionally active signature after 2 days of treatment, as revealed by their FAIRE-associated promoter status, while the remaining seven are rather repressed (H3K27me3-associated promoter status) ( Figure 5C ). Interestingly this last group of TFs is composed by players like the T-box family member Tbx18 – known to be regulated by retinoic acid during somitogenesis (Sirbu & Duester, 2006); the transcriptional repressors Hic1 – known to have a role in neural differentiation and tumor suppression in the central nervous system (Rood & Leprince, 2013) - and Hes6 - known to promote cortical neuron differentiation through the repression of the TF Hes1 (Gratton et al , 2003, 6), the mesoderm specific factor Tcf21, the RNA binding protein Csdc2; the Nuclear factor I-C (Nfic) - known to regulate cell proliferation and differentiation in the central nervous system notably by modulating the expression of the miR-200b (Huang et al , 2021), and Zfp827 - also known as ZNF827 - recently shown to negatively regulate neuronal differentiation through the expression of its circular RNA (Hollensen et al , 2020). Importantly, all these repressed factors appear interconnected within the reconstructed GRN and preferentially associated to the RARβ or RARγ receptors ( Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…15 of them present a transcriptionally active signature after 2 d of treatment, as revealed by their FAIRE-associated promoter status, whereas the remaining seven are rather repressed (H3K27me3-associated promoter status) ( Fig 5C ). Interestingly, this last group of TFs is composed of players like the T-box family member Tbx18 (known to be regulated by retinoic acid during somitogenesis [ Sirbu & Duester, 2006 ]), the transcriptional repressors Hic1 (known to have a role in neural differentiation and tumor suppression in the central nervous system [ Rood & Leprince, 2013 ]), Hes6 (known to promote cortical neuronal differentiation through the repression of the TF Hes1 [ Gratton et al, 2003 ]), the mesoderm-specific factor Tcf21 , the RNA binding protein Csdc2 , the nuclear factor IC ( Nfic ; known to regulate cell proliferation and differentiation in the central nervous system notably by modulating the expression of the miR-200b [ Huang et al, 2021 ]) and Zfp827 (also known as ZNF827) recently shown to negatively regulate neuronal differentiation through the expression of its circular RNA ( Hollensen et al, 2020 ). Importantly, all these repressed factors appear interconnected within the reconstructed GRN and preferentially associated with the RARβ or RARγ receptors ( Fig 5D ).…”
Section: Resultsmentioning
confidence: 99%